Ditangquan exercises based on safe-landing strategies prevent falls and injury among older individuals with sarcopenia - Li, Zhen-rui; Ma, Yun-jing; Zhuang, Jie; Tao, Xun-chen; Guo, Chao-yang; Liu, Shu-ting; Zhu, Ran-ran; Wang, Jin-xiang; Fang, Lei (Frontiers in Medicine, 2022)
Background Sarcopenia is the age-related loss of skeletal muscle mass and function; it is a risk factor for falls among older individuals. Few studies have focused on training such individuals to adopt a safe-landing strategy that would protect them from fall-related injuries. Ditangquan is a traditional Chinese martial art comprising movements that conform to the principles of safe landing. This study aims to investigate the effectiveness of Ditangquan in preventing fall-related injuries among older individuals with sarcopenia. Methods A total of 70 participants (21 males and 49 females with sarcopenia) between 60 and 80 years of age were recruited from three local communities and randomly assigned to the Ditangquan exercise group (DG) or the control group (CG) in a 1:1 ratio. Three times a week for 24 weeks, both the DG and CG received an hour of conventional exercise and an hour of Ditangquan exercise based on safe landing. Primary outcomes were the modified falls efficacy scale (MFES), the number of falls, and fall injuries; the secondary outcome was the Timed Up & Go (TUG) test. Results The DG had significantly fewer falls (1 vs. 8, P = 0.028) and fall injuries (0 vs. 6, P = 0.025) than the CG. Furthermore, at the end of the study, the DG had a significantly improved MFES (mean difference: 32.17 scores; 95% CI: 21.32, 43.02; P <0.001) and TUGT (mean difference: −4.94 s; 95% CI: −7.95, −1.93; P = 0.002) as compared with the CG. Conclusion Ditangquan exercise based on the safe-landing strategy effectively improves the functional mobility of the elderly, reduces the occurrence of falls and injuries, and increases the individual's confidence in preventing falls.